THE EFFECT OF IMPRISONMENT HISTORY AND ACTIVE ILLICIT DRUG USE ON THE RETENTION RATE OF HIV-POSITIVE METHADONE MAINTENANCE THERAPY CLIENTS IN PRIMARY HEALTH CARE CENTERS, KUANTAN, PAHANG - Aida Roziana Ramlan; Mohamed Nazar, Nor Ilyani (International Journal of Allied Health Sciences, 2019)
Methadone maintenance therapy (MMT) program introduced in Malaysia since 2005 for people who inject drug (PWID) population was a success story. Studies showed that combination of antiretroviral therapy (ART) and MMT also plays an important role for harm reduction program and reduce the spread of new HIV infection by reducing the risky behaviour and suppressing the viral load in HIV infected PWID. However, only 34.6% of people who inject drugs (PWID) received ART, and 45.3% of physicians will defer ART in this population due to a history of imprisonment and active use of illicit drugs. This study was conducted to investigate if imprisonment and active drug use affected the retention rate of MMT clients. All HIV-positive MMT clients’ files (the year 2006 to 2019) from six MMT Clinic in Kuantan were evaluated. The data collected regarding the history of imprisonment and drug use was based on patients’ record and regular urine tests in the MMT clinic. A total of 67 HIV-positive MMT clients were included in the study. A total of 37 (55.2%) clients were started on ART, and 30 clients were on MMT only. This study showed that the number of MMT clients who retained in the MMT program were higher in MMT+ART subgroup (59.5%) compared to MMT only subgroup (20.0%). There were no statistical differences on imprisonment history and positive urine drug tests between the two groups, p = 0.609 and 0.268, respectively. The pre-ART counselling session was higher in MMT+ART compared to MMT only subgroup, p<0.001. In conclusion, despite the history of imprisonment and active illicit drug use, MMT clients should be started on ART to ensure the successfulness of the harm reduction program. Intervention such as pre-ART counselling sessions with MMT clients was an important tool to initiate ART, improved ART adherence and increase the retention in the MMT program.